Pengembangan Panduan Permainan Simulasi Ular Tangga untuk Mencegah Prokrastinasi Akademik Siswa SMK - Flurentin, Elia; Hamibawani, Sausanuz Zakiyyah (Buletin Konseling Inovatif, 2025)
Time discipline is one of the habits that vocational high school students must own. Currently, many vocational high school students have academic procrastination and choose to spend their time doing less valuable activities. This study aims to develop a snakes and ladders simulation game guide to reduce academic procrastination for vocational high school students. This study used the Research and Development model from Borg and Gall, which was adapted into seven steps, namely: data collection, planning, product development, testing, revision based on the results of expert testing, testing of prospective product users, and final product revision. The results of expert tests and tests of prospective product users were analyzed using the average formula. Based on the results of the validity index of the guidance and counseling expert test, learning media, and potential users of the product, it shows very high criteria. It meets very appropriate, useful, easy, and interesting acceptability so that the product is declared very feasible. It can be used to implement group guidance services to prevent academic procrastination.